Cybersecurity Awareness and Digital Skills on Readiness For Change in Digital Banking - Zahiroh, Mun Yah (Institut Agama Islam Negeri Kendari, 2020)
This study will explore the impact of cybersecurity awareness and digital skills on readiness for digital banking change. The study sample is fresh graduates in Indonesia's Islamic Banking. The study used PLS-SEM (Partial Least Squares-Structural Equation Modeling) using Smart-PLS 3.0 software. Research shows that 1) cybersecurity awareness does not impact digital banking readiness for change. 2) digital skills have a positive and essential effect on digital banking readiness for change. This study's implications are expected to facilitate the Islamic Banking department in Indonesia to develop its curriculum by including digital intelligence in the Merdeka Belajar curriculum.